2021
DOI: 10.1002/solr.202100807
|View full text |Cite
|
Sign up to set email alerts
|

All‐Slot‐Die‐Coated Inverted Perovskite Solar Cells in Ambient Conditions with Chlorine Additives

Abstract: The advent of halide perovskite permitted significant progress in the field of III generation photovoltaics (PV), demonstrating a rapid growth of power conversion efficiency (PCE) up to 25.5% during the last decade. [1] This is mainly due to the peculiar properties of halide perovskites for photoelectric conversion: strong absorption in the visible region of the solar light spectrum, [2] defect tolerance, [3] big diffusion lengths of the charge carriers (>1 mm), [4] and tunability of the bandgap in the wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 73 publications
0
35
0
Order By: Relevance
“…In 2021, Le et al demonstrated that the use of Cl-containing additives MACl and FACl was essential for controllable crystallization of perovskite films. 138 Finally, the PCEs reached over 16% and 17% in the related MAPbI 3 and CsFAPbI 3 devices, respectively. Furthermore, minimodules (total effective area 2.1 cm 2 ) displayed a PCE of up to 14.9% (Figure 18e−g).…”
Section: Perovskitementioning
confidence: 93%
See 1 more Smart Citation
“…In 2021, Le et al demonstrated that the use of Cl-containing additives MACl and FACl was essential for controllable crystallization of perovskite films. 138 Finally, the PCEs reached over 16% and 17% in the related MAPbI 3 and CsFAPbI 3 devices, respectively. Furthermore, minimodules (total effective area 2.1 cm 2 ) displayed a PCE of up to 14.9% (Figure 18e−g).…”
Section: Perovskitementioning
confidence: 93%
“…(g) J – V curves of the best-performing MAPbI 3 -based and CsFAPbI 3 -based solar cell modules with an active area of 2.1 cm 2 . Reproduced with permission from ref . Copyright 2022 Wiley.…”
Section: Progress On Additive Engineering Of Perovskitementioning
confidence: 99%
“…Although the fabrication of perovskite solar cells in an air environment has achieved certain efficiencies in a short period of time, the high‐efficiency perovskite solar cells mainly rely on small‐area cells (< 1 cm 2 ), fabricated using a spin‐coating process, which limits the possibility of commercial large‐scale production of perovskite solar cells. [ 36‐39 ] Therefore, it is imperative to develop low‐cost and large‐area fabrication processes to make commercially viable PSCs in the ambient air. Moreover, these cells still face many obstacles before industrial application, such as hysteresis, heavy metal lead, ion migration, and long‐term stability.…”
Section: Introductionmentioning
confidence: 99%
“…According to the areas of PSMs, PSMs can be classified as minimodule (< 200 cm 2 ), submodule (200-800 cm 2 ), small module (800-6500 cm 2 ), standard module (6500-14,000 cm 2 ), and large module (> 14,000 cm 2 ) [28,34]. Various strategies have been developed to deposit large-area perovskite films with high quality, such as blade coating [35,36], slot-die coating [37,38], spray coating [39,40], and inkjet printing [41]. The PSM efficiencies have increased to over 20%, and the module areas have increased from tens to hundreds of square centimeters [34,42,43] (Fig.…”
Section: Introductionmentioning
confidence: 99%